Study of risk management adoption on firm value as effected by board's independence. - Chen, Kaiyu. (2008)
This paper examines the impact of differences in the degree of risk management adoption on firm value. We also consider that board’s independence may affect the adoption of risk management and its subsequent effects on firm value. The sample is chosen from Singapore Stock Exchange (SGX) mainboard listed companies for the year of 2002/2003 and 2003/2004. Within Singapore’s context, there has been an increased adoption of enterprise risk management framework by these listed companies. Given the lack of prior empirical studies done with regards to the relationship between the varying degree of risk management adoption and firm value, we build upon our studies based on the postulations of Meulbroek (2002) and also other prior discussions of risk management and corporate governance with firm value. The main implication of our research is that the emergence and growing importance of risk management is not unfounded. Formal adoption of risk management practices with framework does positively impacts firm value and independence of the board of directors further enhances.